Inferring volatility dynamics and risk premia from the S&P 500 and VIX markets - Chris Bardgett; Elise Gourier; Markus Leippold (Queen Mary University of London, School of Economics and Finance, 2016)
This paper studies the information content of the S&P 500 and VIX markets on the volatility of the S&P 500 returns. We estimate a flexible affine model based on a joint time series of underlying indexes and option prices on both markets. An extensive model specification analysis reveals that jumps and a stochastic level of reversion for the variance help reproduce risk-neutral distributions as well as the term structure of volatility smiles and of variance risk premia. We find that the S&P 500 and VIX derivatives prices are consistent in times of market calm but contain conflicting information on the variance during market distress.
Keywords: G12; G13; C58; 330; S&P 500 and VIX joint modeling; volatility dynamics; particle filter; variance risk premium